DEVELOPMENT OF E-BOOKLET BASED ON PROBLEM BASED LEARNING ON ACID BASE MATERIAL FOR PROBLEM SOLVING ABILITY - Burhanudin Milama; Safina Adiliyah; Dila Fairusi (EDUSAINS, 2023)
Teaching materials are a source of learning for students. For this reason, efforts are needed to develop teaching materials that accommodate the needs of students in terms of ease of access, attractive presentation, and encouraging student activity. This research focuses on the development of electronic booklets (e-booklets) using the "problem-based learning (PBL)" model on acid-base materials. Research and Development (R&D) with the 4-D model consisting of define, design, and develop was used as this research method, but dissemination stages were not conducted because of limited research time. 34 purposively selected students of SMAN 21 Bekasi City were given a questionnaire to determine the need for e-booklet development at the define stage. Meanwhile, the questionnaire that had been developed at the development stage was validated by 4 experts. After the instrument was deemed feasible, the e-booklet was tested on 34 purposively selected students. The research findings showed that the percentage of the results of the trial of teaching materials to students was 81.53% with very good criteria. This study concludes that the teaching materials developed are suitable for use as a learning resource for students in solving problems on acid-base materials.